Analytic Morrey Spaces and Bloch-Type Spaces. (11th March 2018) - Samuel, Ofori; Wang, Jianfei; Zhao, Yile
Abstract : This paper is devoted to characterizing the boundedness of the Riemann-Stieltjes operators from analytic Morrey spaces to Bloch-type spaces. Moreover, the boundedness of the superposition operator and weighted composition operator on analytic Morrey spaces is discussed, respectively.